Photoshop for 3D artists. (Worcester : 3DTotal Publishing, 2011)
Whatever 3D software artists use, Photoshop remains a key tool throughout the production pipeline. The techniques presented in Photoshop for 3D Artists: Volume 1 are intended to show how 2D techniques can be seamlessly blended into the 3D production pipeline, resulting in a high quality image and a versatile and streamlined workflow. The book offers artists the chance to learn from a variety of top professionals, such as Andrzej Sykut, Fabio M. Ragonha, and Zoltan Korcsok, who willingly share the tips and tricks that they have developed over years of working in the 3D industry. The tutorials in Photoshop for 3D Artists: Volume 1 cover a variety of different subjects, from the initial concept stage through to post-production. Previz and concepts are explored, showing the advantages of using Photoshop to plan and visualize projects. Combining library images in Photoshop to create custom textures is also featured, as well as how Photoshop can be used as an efficient alternative to lengthy render tests by focusing on compositing passes, adding particle effects, and improving light and color adjustments. These post-production techniques are becoming increasingly popular within the industry as Photoshop becomes a more powerful and time-saving tool, enabling almost every 3D artist to enhance their final renders. With the expertise of individual contributors, the clearly written tutorials, and work-in-progress images, Photoshop for 3D Artists: Volume 1 is a timeless resource for veteran and beginner artists alike.
V. 1. Enhance your 3D renders! Previz, texturing and post production.
Includes index.
Keywords: Adobe Photoshop; Computer graphics; Three-dimensional display systems